Historians Shield and the Politics of Ekphrasis - Ivić, Nenad (Array, 2000)
This paper consists of three parts: the first deals with Graco-Roman tradition of visual representation in historiography, the second describes the medieval adaptation of rhetoric to a Christian historical perspective (the representatiton of the invisible hand of God), the third discusses the changes brought by the transformation of historiography into proto science and science and the role of tableaux images and diagrams in the constitution of truth value of modern historical discourse. Offered as ultimate truths of the privileged relation of historical discourse to reality, tableaux, images and diagrams are shown to represent techniques of argumentation by which the discourse justifies its truth claims.